Metafora dalam Puisi Ogura Hyakunin Isshu Karya Rokkasen - Rafly Adithya, Ismail; Darni Enzimar, Putri; Idrus, Idrus (NAWA: Journal of Japanese Studies, 2026)
This study is concerned with the use of metaphorical language in the poems of the Rokkasen in Ogura Hyakunin Isshu, with a focus on identifying image-based classifications and conceptual meanings. Metaphor is understood as a cognitive mechanism that connects two domains sharing similar characteristics, thereby creating meanings that extend beyond literal expression. A descriptive qualitative approach is employed in this study. In this research, selected poems by the Rokkasen are analyzed. The data were collected through the Uninvolved Conversation Observation technique supported by systematic note-taking. The analysis applies the Referential Identity Method, and the findings are presented using both formal and informal descriptive techniques. The theoretical framework draws on Lakoff and Johnson’s Conceptual Metaphor Theory to explain metaphorical meaning and Ullman’s Image Classification Theory to categorize metaphorical imagery. The results reveal three main types of metaphorical imagery—Anthropomorphic Character, Abstract-to-Concrete Image, and Animal Character—as well as two types of conceptual metaphor: Structural and Ontological. These metaphors reflect central themes commonly found in classical Japanese poetry, particularly love, life, and religion.